Democratic Republic of the Congo : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
The Democratic Republic of the Congo (DRC) has the third-largest land area in Africa with a population of about 50 million. This paper elaborates on specific issues concerning the economic policies of the DRC, the former Zaire, through end-2000. An overview of the country's situation is also provided. The phenomenon of hyperinflation is analyzed. The study also contains a description of the country's exchange and trade system. The appendix updates available statistical information about recent economic and financial developments in the DRC.